Pengembangan Video Animasi Berbasis Pembelajaran Flipped Classroom Pelajaran IPS Untuk Meningkatkan Hasil Belajar Siswa - Sidabutar, Marta Juliati; Budiarta, Kustoro; Rahmadana, Muhammad Fitri (Jayapangus Press, 2024)
Learning media is an important component in the learning process and greatly influences student learning outcomes. Based on interviews and field studies, it was found that teachers lack knowledge and skills regarding interactive learning media so that classroom learning is still limited to the application of conventional media, namely whiteboards and textbooks. So students are less interested in participating in the social sciences learning process and this results in low learning outcomes. The aim of carrying out the research is to develop interactive media in the form of animated videos that are integrated with flipped classroom social studies learning in order to improve the learning outcomes of class VIII students at MTs Negeri 4 Mandailing Natal. This research is a type of R&D that applies the ADDIE model. The research location is at MTs Negeri 4 Mandailing Natal, with the subject being class VIII students. Data was collected through questionnaires and test questions. The data analysis technique uses media feasibility analysis and media effectiveness on social studies learning outcomes. The research results from media validators, material validators, design validator experts, social studies teachers and students were 89.43% with the criteria